2010
DOI: 10.1111/j.1365-2605.2009.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy and DNA fragmentation in morphologically abnormal sperm

Abstract: In light of the relative success of ICSI in the treatment of male infertility, much importance has been made to the selection of morphologically viable sperm. However, correlation between specific sperm morphology and chromosomal abnormalities is still relatively limited and less is known about the connection between sperm morphology and DNA integrity. Sperm obtained from isolated teratozoospermic men (n = 10) and control men (n = 9) were analysed using FISH (for chromosomes 13, 18, 21, X and Y) and TUNEL assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 97 publications
(155 reference statements)
7
46
1
4
Order By: Relevance
“…In the present study too the DFI was significantly higher in morphological abnormal groups compared with normal group. These findings are in agreement with previous studies conducted on infertile patients by several authors [32,[39][40][41]. Abnormal head sperm morphology was also shown to have a negative correlation with sperm motility parameters [21,43,44].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study too the DFI was significantly higher in morphological abnormal groups compared with normal group. These findings are in agreement with previous studies conducted on infertile patients by several authors [32,[39][40][41]. Abnormal head sperm morphology was also shown to have a negative correlation with sperm motility parameters [21,43,44].…”
Section: Discussionsupporting
confidence: 93%
“…Later studies by Sheikh et al also confirmed that DNA fragmentation rate was higher in sperms with abnormal morphology [32]. Further studies by Tang et al reported specific abnormal forms such as tapered and amorphous forms had higher rates of chromosomal abnormalities and DNA fragmentation [40]. Recently, Daris et al further proved that specific head abnormalities, especially amorphous heads had elevated degree of DNA fragmentation [41].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Abdelrazik et al [50] analyzed sperm morphology using computer assisted morphometry, and demonstrated that spermatozoa with several abnormal forms (in particular amorphous and micro heads) containing immature chromatin and higher DNA fragmentation rate compared with other forms of head abnormalities resulting in an increase in aneuploidy incidence and mutations in the germ line [44,51]. In the present study, it was demonstrated that DNA fragmentation was significantly higher in teratozoospermic men compared with normozoospermic men, similar to the results shown by several authors [44,48,50,52,53].…”
Section: Discussionsupporting
confidence: 78%
“…In assisted reproduction programs, several studies show that high levels of sperm DNA fragmentation are related to lower pregnancies rates either natural or using IUI, IVF or ICSI procedures [54][55][56][57] and higher aneuploidies rates in embryos [52,58,59]. Greco et al [60] reported 29 ICSI cycles in which the percentage of DNA-fragmented spermatozoa, detected by TUNEL assay, was >15%; only two pregnancies and no births were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal tails (two-tailed, bent tails, irregular tails) are associated to chromosome 13 disomy, supernumerary chromosomal abnormalities and the cytoskeletal abnormalities (including centriolar defects) [57].…”
Section: Abnormalities Of the Tailmentioning
confidence: 99%